2015
DOI: 10.1016/j.sbspro.2015.04.619
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Adaptive Web-based Intelligent Tutoring System Using Mastery Learning Technique

Abstract: In this paper, we present an Adaptive Web-Based Intelligent Tutoring System using Mastery Learning Technique. According to the level of student knowledge, this system was adapted rule-based techniques and student profiling to generate lessons and tests for them and the system was automatically adjusted suitably adaptive lessons and tests for student when he/she can pass a specified test. This prototype was designed for enhancement JAVA Programming Language Courses in Suan Sunandha Rajabhat University, Thailand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…In the meantime, students were reflected with the feedback given while monitoring their learning status. These results agreed with previous studies showing that the students felt the learning system useful once they received meaningful learning activities according to their actuality of learning (Furo, 2014;Kularbphettong et al, 2015;Lin et al, 2013). While Chookaew et al (2014), Hsu et al (2013), andSong et al (2012) reported that students' personality (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In the meantime, students were reflected with the feedback given while monitoring their learning status. These results agreed with previous studies showing that the students felt the learning system useful once they received meaningful learning activities according to their actuality of learning (Furo, 2014;Kularbphettong et al, 2015;Lin et al, 2013). While Chookaew et al (2014), Hsu et al (2013), andSong et al (2012) reported that students' personality (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to the impact of e-assessments in mathematics, the majority of the studies show that e-assessments with formative feedback contribute to student learning and improve student performance on the final course exam (Varsavsky 2004;Roth et al 2008;Ruokokoski 2009;Rasila et al 2010;Angus and Watson 2009;Huisman and Reedijk 2012;Rivera et al 2013;White et al 2014;Pacheco-Venegas et al 2015.). Research confirms the positive effects of the implementation of the PSI pedagogy in mathematics and programming higher education by the use of video clips and e-assessments (Rae and Samuels 2011;Shafie et al 2010;Kularbphettong et al 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Paiva et al (2015) present the project design features, its development and implementation, evaluation of the tools used and results of studies with the students involved in the project. This paper describes the design, development, implementation and evaluation of an intelligent online tutoring system (TS) (Chrysafiadi and Virvou 2013;Kularbphettong et al 2015;Zhang et al 2014) designed to teach or to remind math concepts essential for the integration of students of engineering, economics, management, among others, in mathematics higher education. The TS, which we developed in MITO platform, consists of small self-paced modularized units of educational contents including tutorial videos, notes and formative eassessments with personalized feedback.…”
Section: Introductionmentioning
confidence: 99%
“…His model is developed around key concepts, namely: differentiated and individualized practices, monitoring progress, evaluation, and feedback [34]. Mastery learning affirms as well as differentiated instruction that most learners are able to acquire competencies and succeed in their learning.…”
Section: Fig 1 Components Of Differentiationmentioning
confidence: 99%